RELATIONSHIP OF VENTILATION AND WASTE MANAGEMENT WITH ACUTE RESPIRATORY INFECTION EVENT IN BANJARSARI WETAN VILLAGE IN 2021 - Istiqomah; Retno Widiarini; Karina Nur Ramadanintyas (LPPM ITEKES Mahardika, 2022)
Acute Respiratory Infection (ARI) is one of several diseases that attack one part or more of the respiratory tract. The spread of ARI starts from the upper channel to the lower channel. ARI often occupies the top 10 list of diseases in the health center. ARI continues to be a health problem in Indonesia because it has a huge impact on the sufferer, besides that ARI can also trigger the emergence of other diseases. The purpose of this study was to analyze the relationship between ventilation and waste management with the incidence of ARI in Banjarsari Wetan Village in 2021. This study was an observational study using a case control study design, observations and interviews were also used to obtain data. The study population was all ARI patients who were treated at the Polindes. This research uses purposive sampling technique. And Chi-Square Test to analyze the research results. ventilation of the majority of respondents did not meet the criteria as many as 29 (51.8%). Ventilation and waste management were not found to be related to the incidence of ARI in Banjarsari Wetan Village in 2021. The village head and the village midwife of Banjarsari Wetan should be able to carry out house monitoring that can be adjusted to the requirements of a healthy house, besides that, socialization about environmental-based diseases that can occur due to unhealthy home environmental conditions can also be carried out.